Metabolomics analysis of Brazilian and Nigerian Asteraceae species, targeting hyperglycemia-modulating metabolites - Jaiyesimi, Olakunle Adeboye (2019)
Chronic hyperglycemia in the prediabetic stage leads to glucose toxicity and pancreatic β-islet cells damage due to oxidative stress, predisposing subjects to the developement of type 2 diabetes. As a significant global health challenge, the continued search for phytoconstituents with potential to prevent, reduce or delay hyperglycemia and its ultimate progression to type 2 diabetes, amongst other benefits including reduced or absence of side effects, is warranted. This study evaluated 68 Asteraceae species for their in vitro ability to improve glucose-uptake, inhibit both fungal (from Aspergillus oryzae) and porcine pancreatic α-amylases, retard glucose diffusion and scavenge DPPH free radicals. Of the plants investigated, 11 retarded glucose diffusion with Senecio biafrae, Eremanthus veadeiroensis and Vernonia brasiliana being the most active; 37 inhibited fungal α-amylase including Silybum marianum, Acanthospermum hispidum and Nigerian Tithonia diversifolia; 12 inhibited porcine pancreatic α-amylase with the most active being S. marianum, Baccharis gaudichaudiana and Eremanthus veadeiroensis; 36 improved insulin-mediated glucose uptake significantly better than metformin including Micania micrantha, Crassocephalum crepidioides and E. veadeiroensis; and 6 significantly exhibited > 90.0% antioxidant activity including Arnica montana, Baccharis genistelloides, B. gaudichaudiana, Erigeron floribundus, Solidago microglossa and Achillea millefolium. All the extracts were analysed by LC-UV-MS for further metabolomics analyses. The LC-MS chromatograms were processed and the generated marices were analyzed by unsupervised (Hierachical Cluster Analysis and Principal Component Analysis) and supervised (Partial least squarediscriminant analysis) multivariate statistical analysis. Untargeted metabolomics, correlating the metabolic fingerprints with the plants\' observed bioactivities, yielded significant discriminant metabolites for each assay. Flavonoids and their glycosides were revealed as important variables responsible for the antidiabetic as well as antioxidant activities, indicating additional potential for the prevention of diabetes. Such includes apigenin 6-C-arabinoside8-C-glucoside, 6-methoxykaempferol-3-O-glucoside, 5-hydroxy-3,6,7,4\'- tetramethoxyflavone, 5,6,7,4\'-tetramethoxyflavone and 3,4\',6-trimethoxyquercetagetin. This study provides further evidence for the use of untargeted metabolomics for the rapid determination of plant specialized metabolites with bioactive potentials, in this case the reduction or prevention of hyperglycaemia.